Microsoft Visual C♯ 2005 - Sharp, John, 1964- (Step by step (Redmond, Wash.), 2005)
Teach yourself Visual C♯ 2005 fundamentals-one step at a time. With this practical, learn-by-doing tutorial, you get the guidance you need to start creating programs and components in C♯! Discover how to: Work in the Visual Studio 2005 development environmentDeclare variables, call methods, and create operatorsConstruct statements to selectively or repeatedly run your codeCatch and handle exception errorsUse object-oriented concepts to declare classes and objectsWrite destructors to clean up unneeded code and help manage res.